Redox electrode for total iron flow battery and preparation method and application thereof

By pretreating the carbon electrode and uniform loading of metal-carbon loads, the problem of polarization loss in traditional electrodes is solved, and the redox activity and stability of the electrodes are significantly improved, and the electrodes with simple process and low cost are realized Modification effect.

CN119481095APending Publication Date: 2025-02-18CHINA THREE GORGES TECH CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411598113.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-11
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

Traditional carbon electrodes have polarization losses in full iron flow batteries, which affect their activity. The existing modification methods are complex in technology and high in cost, and are not suitable for large-scale promotion.

Method used

By pretreating the carbon electrode, metal-carbon loads are prepared and uniformly loaded on the surface of the carbon electrode, the load is controlled to be 3mg/cm2, and the electrode redox is improved by using ultrasonic treatment and low-temperature drying and other technical means. active.

Benefits of technology

It significantly improves the redox activity of the electrode, improves the cycle life and stability of the battery, has a simple and easy process, a wide range of application, and is suitable for promotion to other liquid flow battery systems.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119481095A_ABST
    Figure CN119481095A_ABST
Patent Text Reader

Abstract

In order to overcome the defects in the prior art, the invention provides a preparation method of a redox electrode for an all-iron flow battery, and the preparation method comprises the following steps: step 1, pretreating a carbon electrode to obtain a pretreated carbon electrode; step 2, preparing a metal-carbon load; step 3, dissolving the metal-carbon load in a solvent to obtain a treatment solution; 4, immersing the pretreated carbon electrode in the treating fluid, and controlling the loading capacity of the metal-carbon load on the carbon electrode to be 3mg / cm < 2 >; and step 5, taking out the carbon electrode loaded with the metal-carbon load, and drying to obtain the redox electrode for the total iron flow battery. According to the redox electrode for the total iron flow battery, the metal-carbon material serves as an electrode load, more reaction sites can be provided for the electrode, the prepared electrode is high in catalytic activity, and the redox activity of the electrode is remarkably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of electrochemical technology, and in particular to a redox electrode for an all-iron liquid flow battery, a preparation method and an application thereof. Background Art

[0002] With the widespread use of renewable energy such as solar and wind energy, their intermittency and instability have become a major challenge. Energy storage technology can capture the excess energy of these energy sources and store it, and release the stored energy when renewable energy cannot meet demand, thereby improving the utilization rate of renewable energy and reducing dependence on traditional energy. Liquid flow batteries, as a very promising large-scale energy storage device, have the characteristics of long cycle life, high safety, and energy and power decoupling, and have received widespread attention.

[0003] Iron-based flow batteries, represented by all-iron flow batteries, use Fe as the active component. They have the advantages of a wide source of active materials, low cost, and high energy density, and have good application prospects in the field of distributed energy storage. Electrodes are the site of redox reactions of active materials in flow batteries, and their electrochemical activity has a key influence on the performance of the battery. Carbon electrodes are considered to be ideal electrode materials for iron-chromium flow batteries because of their high chemical stability, long service life, and wide potential range in highly oxidizing media.

[0004] In practical use, traditional carbon electrodes have various polarization losses that affect their activity. Existing technologies often reduce the polarization of the negative electrode of the battery by doping iron and tin atoms on the surface, while allowing iron to be evenly deposited on the electrode surface, thereby increasing the cycle life of the battery. However, this technical process is complex and the preparation cost is high, making it unsuitable for large-scale promotion. Summary of the invention

[0005] In order to solve the deficiencies of the prior art, the present invention provides a method for preparing a redox electrode for an all-iron liquid flow battery, comprising the following steps:

[0006] Step 1: pretreating the carbon electrode to obtain a pretreated carbon electrode.

[0007] Step 2: preparing metal-carbon support.

[0008] Step 3: dissolving the metal-carbon support in a solvent to obtain a treatment solution.

[0009] Step 4: Immerse the pretreated carbon electrode in the treatment solution and control the loading amount of the metal-carbon load on the carbon electrode to 3 mg / cm 2 .

[0010] Step 5: Take out the carbon electrode loaded with the metal-carbon support, and after drying, obtain the redox electrode for the all-iron liquid flow battery.

[0011] Furthermore, the pretreatment in step 1 includes:

[0012] Step 1.1: Process the carbon electrode into a preset size to obtain a standard carbon electrode.

[0013] Step 1.2: Rinse the standard carbon electrode with deionized water to obtain a water-washed standard carbon electrode.

[0014] Step 1.3: Soak the washed standard carbon electrode in an organic reagent and ultrasonically treat it at a frequency of 80-120 kHz for 40-80 minutes to obtain an ultrasonically treated standard carbon electrode.

[0015] Step 1.4: Place the ultrasonically treated standard carbon electrode in an environment of 180-200° C. for 40-80 minutes to obtain a pretreated carbon electrode.

[0016] Furthermore, the carbon electrode is selected from any one of carbon felt, graphite felt, carbon paper, graphite paper, carbon cloth, and graphite cloth.

[0017] Furthermore, the metal-carbon support in step 2 is prepared by the following method:

[0018] Step 2.1: preparing a metal colloidal solution, wherein the metal is one or more of platinum, ruthenium, rhodium and iridium.

[0019] Step 2.2 Preparation of activated carbon solution.

[0020] Step 2.3 Add the metal colloid solution dropwise into the activated carbon solution at room temperature and stir evenly.

[0021] After the addition in step 2.4 is completed, add deionized water and continue stirring for 40-80 minutes.

[0022] Centrifuge in step 2.5, remove the supernatant and wash alternately with organic reagent and deionized water several times.

[0023] In step 2.6, the metal-carbon support is obtained after freeze-drying.

[0024] Furthermore, the metal colloid solution in step 2.1 is prepared by the following method:

[0025] Step 2.1.1 Mix the metal salt and the solvent solution at room temperature and stir until the metal salt is completely dissolved to obtain a metal salt solution.

[0026] Step 2.1.2: Add a pH adjuster dropwise to the metal salt solution to adjust the pH of the metal salt solution to 7-9.

[0027] Step 2.1.3: Treat at 160±5℃ for 40-60 minutes under inert atmosphere.

[0028] Step 2.1.4: Cool to room temperature to obtain a metal colloidal solution.

[0029] Furthermore, the metal salt is chloroplatinic acid hexahydrate, the solvent is ethylene glycol, and the pH adjuster is an ethylene glycol solution of sodium hydroxide.

[0030] Furthermore, when the metal colloid solution is added dropwise to the activated carbon solution as described in step 2.3, the molar ratio of metal to carbon is controlled to be 1:131-133.

[0031] Furthermore, when the pretreated carbon electrode is immersed in the treatment solution in step 4, the content of the metal-carbon load in the treatment solution is 3 mg / mL.

[0032] Furthermore, when the pretreated carbon electrode is immersed in the treatment solution in step 4, ultrasonic treatment with a frequency of 80-120 kHz is applied simultaneously.

[0033] Furthermore, the drying method in step 5 is: drying at 70±3° C. for 20-28 hours.

[0034] In addition, the present invention also provides a redox electrode for an all-iron liquid flow battery, which is prepared by the above-mentioned method for preparing a redox electrode for an all-iron liquid flow battery.

[0035] The third object of the present invention is to provide a redox electrode for an all-iron liquid flow battery for use as a positive electrode or a negative electrode in the all-iron liquid flow battery.

[0036] The beneficial effects of the present invention are:

[0037] 1. The redox electrode for the all-iron liquid flow battery of the present invention uses metal-carbon material as the electrode load, which can provide more reaction sites for the electrode. The prepared electrode has high catalytic activity and significantly improves the redox activity of the electrode.

[0038] 2. The metal-carbon catalyst in the redox electrode for the all-iron liquid flow battery of the present invention has high stability and good affinity with the electrode matrix, thereby ensuring high stability of the electrode in the all-iron liquid flow battery system.

[0039] 3. Compared with the existing electrode modification methods, the method of the present invention is simple and easy to operate, has significant improvement effect, good stability, wide application range, and can be extended to other liquid flow battery systems. BRIEF DESCRIPTION OF THE DRAWINGS

[0040] Figure 1 TEM image of the platinum-carbon support obtained in the embodiment of the present invention;

[0041] Figure 2A cyclic voltammetric comparison diagram of the positive electrode original carbon felt electrode and the redox electrode for the all-iron liquid flow battery obtained in the embodiment of the present invention in the positive electrode electrolyte;

[0042] Figure 3 It is a comparison diagram of the cyclic voltammetry of the original carbon felt electrode of the negative electrode and the redox electrode for the all-iron liquid flow battery obtained in the embodiment of the present invention in the negative electrode electrolyte. DETAILED DESCRIPTION

[0043] The present invention will now be described in further detail with reference to the accompanying drawings. These drawings are simplified schematic diagrams, which only illustrate the basic structure of the present invention in a schematic manner, and therefore only show the components related to the present invention.

[0044] Please note that the terms "above", "below", "left", "right", "top", "top", "bottom", "bottom", etc. used in the present invention to describe the positional relationship do not represent the absolute positional relationship between the modules / components / assemblies / components / parts, but the relative positional relationship between the modules / components / assemblies / components / parts.

[0045] The present invention exemplarily provides a method for preparing a redox electrode for an all-iron liquid flow battery, comprising the following steps:

[0046] Step 1: pretreating the carbon electrode to obtain a pretreated carbon electrode.

[0047] Step 2: preparing metal-carbon support.

[0048] Step 3: dissolving the metal-carbon support in a solvent to obtain a treatment solution.

[0049] Step 4: Immerse the pretreated carbon electrode in the treatment solution and control the loading amount of the metal-carbon load on the carbon electrode to 3 mg / cm 2 .

[0050] Step 5: Take out the carbon electrode loaded with the metal-carbon support, and after drying, obtain the redox electrode for the all-iron liquid flow battery.

[0051] The present invention introduces a metal-carbon support on the electrode surface through a specific preparation method, which can reduce the activation energy of the reaction and effectively promote the electrode reaction. The metal-carbon support can provide active sites, adsorb reactants and accelerate the reaction rate.

[0052] The present invention illustratively provides a pretreatment method described in step 1, which specifically includes:

[0053] Step 1.1: Process the carbon electrode into a preset size to obtain a standard carbon electrode.

[0054] Step 1.2: Rinse the standard carbon electrode with deionized water to obtain a water-washed standard carbon electrode.

[0055] Step 1.3: Soak the washed standard carbon electrode in an organic reagent and ultrasonically treat it at a frequency of 80-120 kHz for 40-80 minutes to obtain an ultrasonically treated standard carbon electrode.

[0056] Step 1.4: Place the ultrasonically treated standard carbon electrode in an environment of 180-200° C. for 40-80 minutes to obtain a pretreated carbon electrode.

[0057] Through this method, on the one hand, the surface of the carbon electrode can be treated to a clean state by treatment with deionized water and organic reagents, and on the other hand, reaction active points can be formed on the surface of the carbon electrode through specific ultrasonic and heat treatments, so that a stable bond can be formed with the metal-carbon support in the subsequent steps, thereby improving the stability of the modified electrode.

[0058] The present invention exemplarily provides a carbon electrode, specifically any one of carbon felt, graphite felt, carbon paper, graphite paper, carbon cloth, and graphite cloth, preferably a carbon felt electrode.

[0059] The present invention illustratively provides a metal-carbon support described in step 2, which is prepared by the following method:

[0060] Step 2.1: prepare a metal colloidal solution, wherein the metal is one or more of platinum, ruthenium, rhodium and iridium, preferably platinum.

[0061] Step 2.2 Preparation of activated carbon solution.

[0062] Step 2.3 Add the metal colloid solution dropwise into the activated carbon solution at room temperature and stir evenly.

[0063] After the addition in step 2.4 is completed, add deionized water and continue stirring for 40-80 minutes.

[0064] Centrifuge in step 2.5, remove the supernatant and wash alternately with organic reagent and deionized water several times.

[0065] In step 2.6, the metal-carbon support is obtained after freeze-drying.

[0066] Metal-carbon and specific reactants are prepared by combining specific metals with activated carbon, which can be combined with the activated surface of the carbon electrode in the subsequent steps to form a stable loading structure. The loaded metal can provide active sites, thereby reducing the activation energy of the reaction and effectively promoting the electrode reaction.

[0067] In addition, the applicant has found through research that the technical method used in the prior art for preparing metal-carbon composites is usually to drop the carbon solution into the metal colloid solution drop by drop, the purpose of which is to make the excess metal salt in the metal colloid solution react with carbon in the process of dropping the carbon solution, and attach or chemically bond to the surface of the carbon material, so that the metal salt can be more attached to the surface of the carbon material. However, the metal-carbon composite prepared by this method, on the one hand, has a large difference in the content of metal salt attached to the surface of the carbon material, and the metal salt attached to the surface of the carbon material that is first dropped is more than the carbon material that is dropped later, so it will cause a large difference in the reaction activity of electrodes in different regions. The common means of overcoming the problem in the prior art is to increase the content of metal salts, but metal salts are generally precious metals, and their cost price is relatively high. Increasing the content of metal salts also increases the preparation cost, and the attachment of excessive metal salts will also lead to a decrease in performance. On the other hand, the carbon material with too much metal salt attached to the metal-carbon composite prepared by this method is more difficult to stably attach to the surface of the carbon electrode, which will lead to a gradual decrease in the electrode reaction ability and a decrease in the stability of the electrode.

[0068] The present invention changes the preparation method of the traditional technology and adopts the method of adding the metal colloid solution drop by drop into the activated carbon solution, that is, in the process of adding the metal colloid solution, the excess carbon in the carbon solution reacts with the metal salt, so that the metal salt can be relatively evenly loaded on the surface of the carbon material. Therefore, on the one hand, a metal-carbon composite with evenly loaded metal salt can be obtained without increasing the content of the metal salt. On the other hand, the prepared metal-carbon composite has good adhesion stability with the carbon electrode, and the modified electrode can be used stably for a long time.

[0069] In addition, the applicant has found through research that high temperature drying treatment will affect the reactivity of metal-carbon supports to a certain extent. The present invention can effectively solve the influence of high temperature drying treatment on metal-carbon supports by freeze drying the metal-carbon supports in the final drying stage.

[0070] The present invention illustratively provides the metal colloid solution described in step 2.1, which is prepared by the following method:

[0071] Step 2.1.1 Mix the metal salt and the solvent solution at room temperature and stir until the metal salt is completely dissolved to obtain a metal salt solution.

[0072] Step 2.1.2: Add a pH adjuster dropwise to the metal salt solution to adjust the pH of the metal salt solution to 7-9, preferably 8.

[0073] Step 2.1.3: Treat at 160±5℃ for 40-60 minutes under inert atmosphere.

[0074] Step 2.1.4: Cool to room temperature to obtain a metal colloidal solution.

[0075] The metal salt is chloroplatinic acid hexahydrate, the solvent is ethylene glycol, and the pH regulator is an ethylene glycol solution of sodium hydroxide.

[0076] The method can prepare a metal colloid solution suitable for the reaction system of the present invention.

[0077] The present invention illustratively provides a method for controlling the molar ratio of metal to carbon when the metal colloid solution is added dropwise to the activated carbon solution in step 2.3, specifically: controlling the molar ratio of metal to carbon to be 1:131-133.

[0078] Compared with the prior art technical solution of controlling the molar ratio of metal to carbon to be close to 1:10-20, the present invention can significantly reduce the molar ratio of metal to carbon by adjusting the dripping method. While ensuring that the modified electrode has good performance, the amount of precious metal required for modification is significantly reduced, thereby reducing the modification cost, making the modified electrode have a better prospect for large-scale application.

[0079] The present invention provides an exemplary method of immersing the pretreated carbon electrode in the treatment solution in step 4, wherein the content of the metal-carbon load in the treatment solution is 3 mg / mL. At this concentration, the carbon electrode can better control the loading amount of the metal-carbon load on the carbon electrode, making it easier to maintain 3 mg / cm 2 .

[0080] The present invention exemplarily provides a method of immersing the pretreated carbon electrode in the treatment solution in step 4 while applying ultrasonic treatment at a frequency of 80-120kHz. This method can significantly speed up the immersion treatment, reducing the immersion treatment time to about 20% of the original treatment time.

[0081] The present invention exemplarily provides a drying method for step 5, which is: drying at 70±3°C for 20-28 hours. Drying the treated electrode at this temperature can, on the one hand, fully volatilize the water, and on the other hand, allow the metal-carbon load to react with the carbon electrode to a certain extent on the surface, thereby improving the loading stability of the metal-carbon load.

[0082] The present invention exemplarily provides a redox electrode for an all-iron liquid flow battery, and the electrode is prepared by using the above-mentioned method for preparing a redox electrode for an all-iron liquid flow battery.

[0083] The present invention exemplarily provides a redox electrode for an all-iron liquid flow battery for use as a positive electrode or a negative electrode in the all-iron liquid flow battery.

[0084] The technical effects of the present invention are further described below in conjunction with specific embodiments.

[0085] Example 1

[0086] A redox electrode for an all-iron liquid flow battery, wherein carbon felt is used as a carbon electrode, platinum is used as a loaded metal, and activated carbon is used as a loaded carbon. The electrode is prepared by the following method:

[0087] Step 1: Cut the length, width and thickness of the carbon felt electrode to 15 mm, 10 mm and 2 mm respectively, and wash with water to remove solid and water-soluble substances on the surface of the carbon felt electrode. Use acetone to remove organic impurities in the carbon felt electrode and perform ultrasonic treatment. The ultrasonic frequency is 100 kHz, and the ultrasonic treatment time is 60 minutes. Finally, treat the carbon felt at 200°C for 60 minutes to obtain a pretreated carbon felt electrode.

[0088] Step 2: preparing a platinum-carbon support; specifically comprising:

[0089] (1) 2.0 g of chloroplatinic acid hexahydrate was mixed with 100 mL of ethylene glycol solution and stirred at room temperature until completely dissolved. A 0.30 mol / L sodium hydroxide ethylene glycol solution was prepared and the sodium hydroxide ethylene glycol solution was added dropwise to the mixed solution, the pH was adjusted to 8, and the mixture was heated to 160° C. under a nitrogen atmosphere and maintained for 60 minutes. After cooling to room temperature, a uniform and stable brown platinum colloidal solution was obtained, which was a metal colloidal solution.

[0090] (2) 2.0 g of activated carbon was uniformly dispersed in 100 ml of ethylene glycol solution to obtain an activated carbon solution.

[0091] (3) Add 37.50 g of the metal colloid solution obtained in step (1) dropwise into the activated carbon solution obtained in step (2) at room temperature and stir evenly.

[0092] (4) After the dropwise addition was completed, deionized water was added and stirring was continued for 60 minutes.

[0093] (5) Centrifuge, remove the supernatant and wash alternately with ethanol and deionized water for 5 times.

[0094] (6) After freeze-drying in a vacuum freeze dryer for 24 hours, the platinum-carbon support is obtained.

[0095] Step 3: Add the platinum-carbon support to the ethylene glycol solution and perform ultrasound for 60 minutes to obtain a uniform slurry, wherein the content of the platinum-carbon support in the slurry is 3 mg / mL.

[0096] Step 4: Immerse the pretreated carbon felt electrode in the treatment solution obtained in step 3, and control the loading amount of the platinum-carbon support on the carbon felt electrode to be 3 mg / cm 2 ;

[0097] Step 5: Take out the carbon felt electrode loaded with the platinum-carbon support, and after drying, obtain the redox electrode for the all-iron liquid flow battery.

[0098] The TEM image of the platinum-carbon support obtained in Example 1 is as follows Figure 1 As shown, it can be seen that since the present invention changes the traditional preparation process of platinum-carbon support, the platinum metal is uniformly attached to the surface of the carbon felt electrode in a more uniform particle form, and there is almost no platinum metal agglomeration phenomenon. Therefore, on the one hand, the reaction activity of the obtained platinum-carbon support is excellent, and on the other hand, the protruding metal agglomerates will not hinder the loading stability of the platinum-carbon support on the carbon felt electrode.

[0099] The cyclic voltammetric data of the electrode loaded with platinum-carbon material obtained in Example 1 and the original carbon felt electrode are compared. Figure 2 and Figure 3 The cyclic voltammetry performance test was performed using a Biologic VMP3 electrochemical workstation. A three-electrode system was used during the test, with the working electrode being the catalyst-loaded carbon felt electrode or the original carbon felt electrode in this embodiment, the counter electrode being a platinum wire, the reference electrode being an Ag / AgCl electrode (filled with a saturated KCl solution), the positive electrode electrolyte being 10mM K4Fe(CN)6in 2MNaOH, the negative electrode electrolyte being 10mM FeCl3+20mM BIS-TRIS+4M NaOH, the scan rate being 20mV / s, and argon gas being continuously passed during the cyclic voltammetry test to prevent the electrolyte from being oxidized.

[0100] from Figure 2 and Figure 3 It can be seen that the original carbon felt has very poor activity, and the reduction peak of the electrode modified by the present invention becomes obvious, and the peak currents of the oxidation peak and the reduction peak are further increased. The high-performance carbon felt electrode prepared by the present invention has the largest peak current, and exhibits superior electrochemical activity compared to the original carbon felt, and is applicable to both positive and negative electrodes, further indicating the universality and scalability of the electrode prepared by the present invention for improving the electrochemical reaction activity of iron-based liquid flow batteries.

[0101] Based on the above ideal embodiments of the present invention, the relevant staff can make various changes and modifications without departing from the technical concept of the present invention through the above description. The technical scope of the present invention is not limited to the contents of the specification, and its technical scope must be determined according to the scope of the claims.

Claims

1. A method for preparing a redox electrode for an all-iron liquid flow battery, characterized in that: The steps include: Step 1: pretreating the carbon electrode to obtain a pretreated carbon electrode; Step 2: preparing a metal-carbon support; Step 3: dissolving the metal-carbon support in a solvent to obtain a treatment solution; Step 4: Immerse the pretreated carbon electrode in the treatment solution and control the loading amount of the metal-carbon load on the carbon electrode to 3 mg / cm 2 ; Step 5: Take out the carbon electrode loaded with the metal-carbon support, and after drying, obtain the redox electrode for the all-iron liquid flow battery.

2. The method for preparing a redox electrode for an all-iron liquid flow battery according to claim 1, characterized in that: The pretreatment in step 1 includes: Step 1.1: Processing the carbon electrode into a preset size to obtain a standard carbon electrode; Step 1.2: rinse the standard carbon electrode with deionized water to obtain a water-washed standard carbon electrode; Step 1.3: soaking the washed standard carbon electrode with an organic reagent, and ultrasonically treating it at a frequency of 80-120 kHz for 40-80 minutes to obtain an ultrasonically treated standard carbon electrode; Step 1.4: Place the ultrasonically treated standard carbon electrode in an environment of 180-200° C. for 40-80 minutes to obtain a pretreated carbon electrode.

3. The method for preparing a redox electrode for an all-iron liquid flow battery according to any one of claims 1 or 2, characterized in that: The carbon electrode is selected from any one of carbon felt, graphite felt, carbon paper, graphite paper, carbon cloth and graphite cloth.

4. The method for preparing a redox electrode for an all-iron liquid flow battery according to claim 1, characterized in that: The metal-carbon support in step 2 is prepared by the following method: Step 2.1: preparing a metal colloidal solution, wherein the metal is one or more of platinum, ruthenium, rhodium, and iridium; Step 2.2 preparing an activated carbon solution; Step 2.3 Add the metal colloid solution dropwise into the activated carbon solution at room temperature and stir evenly; After step 2.4, add deionized water and continue stirring for 40-80 minutes; Step 2.5: Centrifuge, remove the supernatant and wash several times with organic reagent and deionized water alternately; In step 2.6, the metal-carbon support is obtained after freeze-drying.

5. The method for preparing a redox electrode for an all-iron liquid flow battery according to claim 4, characterized in that: The metal colloid solution in step 2.1 is prepared by the following method: Step 2.1.1: mixing the metal salt and the solvent solution at room temperature and stirring until the metal salt is completely dissolved to obtain a metal salt solution; Step 2.1.2: adding a pH regulator to the metal salt solution to adjust the pH of the metal salt solution to 7-9; Step 2.1.3: Treat at 160±5°C for 40-60 minutes under an inert atmosphere; Step 2.1.4: Cool to room temperature to obtain a metal colloidal solution.

6. The method for preparing a redox electrode for an all-iron liquid flow battery according to claim 5, characterized in that: The metal salt is chloroplatinic acid hexahydrate, the solvent is ethylene glycol, and the pH regulator is an ethylene glycol solution of sodium hydroxide.

7. The method for preparing a redox electrode for an all-iron liquid flow battery according to claim 4, characterized in that: When the metal colloid solution is added dropwise to the activated carbon solution as described in step 2.3, the molar ratio of metal to carbon is controlled to be 1:131-133.

8. The method for preparing a redox electrode for an all-iron liquid flow battery according to claim 1, characterized in that: When the pretreated carbon electrode is immersed in the treatment solution in step 4, the content of the metal-carbon load in the treatment solution is 3 mg / mL.

9. The method for preparing a redox electrode for an all-iron liquid flow battery according to claim 1, characterized in that: When the pretreated carbon electrode is immersed in the treatment solution as described in step 4, ultrasonic treatment with a frequency of 80-120kHz is applied simultaneously.

10. The method for preparing a redox electrode for an all-iron liquid flow battery according to claim 1, characterized in that: The drying method in step 5 is: drying at 70±3°C for 20-28 hours.

11. A redox electrode for an all-iron liquid flow battery, characterized in that: The electrode is prepared by the method for preparing a redox electrode for an all-iron liquid flow battery according to any one of claims 1 to 9.

12. A redox electrode for an all-iron liquid flow battery is used as a positive electrode or a negative electrode in the all-iron liquid flow battery.

Citation Information

Cited By

  • Biomass derived carbon skeleton modified graphite felt electrode and preparation method and application thereof

    CN122202346A